SPECIAL ECONOMIC ZONES AND INVESTMENT PRIVILEGES IN UZBEKISTAN: INCENTIVES FOR FOREIGN INVESTORS - Qadamova Komila Tojiboy qizi, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2026)
This article examines the sectoral structure of free economic zones in the Republic of Uzbekistan and the available benefits and incentives to attract foreign investment.